2022
DOI: 10.1038/s41522-022-00368-y
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with an HIV T-cell immunogen induces alterations in the mouse gut microbiota

Abstract: The gut microbiota is emerging as a crucial factor modulating vaccine responses; however, few studies have investigated if vaccines, in turn, can alter the microbiota and to what extent such changes may improve vaccine efficacy. To understand the effect of T-cell vaccination on the gut microbiome, we administered an HIV-1 T-cell immunogen (HTI arm) or PBS (control, Mock arm) to C57Bl/6 mice following a heterologous prime-boost scheme. The longitudinal dynamics of the mice gut microbiota was characterized by 16… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Only a few studies have investigated whether the administration of vaccines is associated with changes in the composition of the intestinal microbiota 12,[20][21][22][23][24][25][26] , and whether the changes induced by vaccination, in turn, influence vaccine immunogenicity 20 . These studies have reported inconsistent results.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Only a few studies have investigated whether the administration of vaccines is associated with changes in the composition of the intestinal microbiota 12,[20][21][22][23][24][25][26] , and whether the changes induced by vaccination, in turn, influence vaccine immunogenicity 20 . These studies have reported inconsistent results.…”
mentioning
confidence: 99%
“…A recent study using metagenomic sequencing, reported that the intramuscular administration of an inactivated and an mRNA SARS-CoV-2 vaccine was associated with lower bacterial diversity, an increase in the relative abundance of Bacteroides caccae and a decrease in the relative abundance of Clostridiales (Coprococcus comes, Dorea longicatena and Ruminococcus obeum) in the intestinal microbiota one month after vaccination 20 . Animal studies have also shown that the administration of vaccines can lead to changes in the intestinal microbiota: in mice, an increase in the relative abundance of Bacteroides has been reported after intramuscular vaccination with a Mycobacterium tuberculosis vaccine 25 and compared with mice vaccinated with a placebo, mice vaccinated intramuscularly with an HIV T-cell immunogen had a higher relative abundance of Clostridiales (Eubacterium xylanophilum, Roseburia and Ruminococcus) 26 . In rhesus macaques, the intradermal administration of a combined HIV-1 DNA/protein vaccine has been shown to lead to an increase in the Firmicutes/Bacteroidetes ratio and a decreased relative abundance of Prevotella, Alloprevotella, Bacteroides, Acetobacteroides, Falsiporphyromonas and Anaerocella.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Enterorhabdus promotes LPS‐induced intestinal inflammation and dysbiosis in mice 39 . Eubacterium._xylanophilum_group is named as the main contributor of anti‐inflammatory metabolites such as short‐chain fatty acids 49 . Here, the relative abundance of Escherichia‐Shigella and Enterorhabdus in the gut microbiota of NOD mice injected with T cells co‐cultured with UC‐MSCs or UC‐MSCs‐exo was reduced, while the relative abundance of Eubacterium._xylanophilum_group was increased.…”
Section: Discussionmentioning
confidence: 91%